Natural attenuation can lead to environmental resilience in mine environment. (June 2020) - Dore, Elisabetta; Fancello, Dario; Rigonat, Nicola; Medas, Daniela; Cidu, Rosa; Da Pelo, Stefania; Frau, Franco; Lattanzi, Pierfranco; Marras, Pier Andrea; Meneghini, Carlo; Podda, Francesca; Rimondi, Valentina; et al.
Abstract: Four streams flowing in the Iglesiente and Arburese mine districts (SW Sardinia, Italy), exploited for zinc (Zn) and lead (Pb) extraction from sulphides and secondary non-sulphide mineralization (calamine ores), have been studied combining investigations from the macroscale (hydrologic tracer techniques) to the microscale (X-ray powder diffraction, scanning electron microscopy, X-ray absorption spectroscopy). In the investigated area, concerns arise from release of metals to water during weathering of ore minerals and mine-waste. Specifically, Zn is observed at extremely high concentrations (10s of mg/L or more) in waters in some of the investigated catchments. The results from synoptic sampling campaigns showed marked differences of Zn loads, from 6.3 kg/day (Rio San Giorgio) to 2000 kg/day (Rio Irvi). Moreover, natural attenuation of metals was found to occur i) through precipitation of Fe compounds (Fe oxy/hydroxides and "green rust"), ii) by means of the authigenic formation of metal sulphides promoted by microbial sulphate reduction, iii) by metal intake in roots and stems of plants ( Phragmites australis and Juncus acutus ) and by immobilization in the rhizosphere, and iv) by cyanobacterial biomineralization processes that lead to formation of Zn-rich phases (hydrozincite and amorphous Zn-silicate). The biologically mediated natural processes that lead to significant abatement and/or reduction of metal loads, are the response of environmental systems to perturbations caused from mine activities, and can be considered part of the resilience of the system itself. The aim of this study is to understand the effect of these processes on the evolution of the studied systems towards more stable and, likely, resilient conditions, e.g. by limiting metal mobility and favouring the improvement of the overall quality of water. The understanding of how ecosystems adapt and respond to contamination, and which chemical and physical factors control these natural biogeochemical barriers, can help to plan effective remediation actions. Highlights: Resilient conditions limit metal mobility. Understanding of how ecosystems adapt and respond to contamination. Chemical and physical factors controlling natural biogeochemical barriers. Planning effective remediation actions.